PENGARUH LIKUIDITAS DAN SOLVABILITAS TERHADAP KINERJA KEUANGAN PADA PT ASPIRASI HIDUP INDONESIA Tbk PERIODE 2014-2024 - Ade Irma Febriyanti; Vega Anismadiyah (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to analyze the influence of Liquidity and Solvency, both partially and simultaneously on Financial Performance at PT Aspirasi Hidup Indonesia Tbk for the 2014-2024 period. The independent variables in this study are Liquidity measured using the Quick Ratio (QR) and Solvency measured using the Debt to Equity Ratio (DER). Meanwhile, the dependent variable is Financial Performance measured using Return On Equity. The research method used in this study is a quantitative method with a descriptive approach. The selected population is the financial statements of PT Aspirasi Hidup Indonesia Tbk, with the samples used being financial statements in the form of balance sheets and income statements for the 2014-2024 period. Based on the research results obtained partially, the liquidity variable has a significant influence on Financial Performance. The results of the study are proven by the significance value (0.022 < 0.05) and the value of │thitung│> ttable (│-2.828│ = 2.828> 2.30600), and the Solvency variable does not have a significant influence on Financial Performance. The results of the study are proven by the significance value (0.247> 0.05) and the value of │thitung│ < ttable (│-1.250│ = 1.250< 2.30600). While simultaneously there is a significant influence between the Liquidity and Solvency variables on Financial Performance. The results of the study are proven by the significance value (0.038 < 0.05) and the value of Fhitung> Ftable (5.052> 4.46).